Shariah and Accounting Principles for Calculating the Actual Cost of Lending Services among Islamic Banks: Case of Malaysia - Saleh, Abdulmajid Obaid Hasan; Al-Shaghdari, Fahd; T Hakami, ahani Ali (2021)
Shariah associations and bodies have permitted Islamic Banks to take the actual cost of lending, that’s was due to the permissibility of differentiating between the loan and the services accompanying its amortization, restriction and follow-up, as these proceedings are not included in the principal of the loan. The Islamic banks differed in applying the concept of actual cost based on a lump sum and a percentage. The academies also differed in the methods of taking this cost, because the fee-based services provided by Islamic banks may bring some legitimate issues related to the imposition of fees or the actual cost. The research adopted the descriptive and analytical approach and the quantitative method by studying the case of Malaysian Islamic banks in accordance to the accounting principles and the related rules